Prediction of Decay Modes for Superheavy Nuclei with Magic Number of Neutrons and Protons - Bai, G. M. C. V.; Revathi, R. (Journal of Scientific Research, 2024)
The Cubic plus Yukawa plus Exponential (CYE) model has been used to study the different decay properties of Superheavy nuclei 298,310114, 306,318122, 308,310124, 310,322126 and compared them with the available theoretical and experimental values. Here, the half-lives of several clusters have been computed that have not yet been detected experimentally. Hopefully, this will assist future research in this area. As a result of comparing the three different decay modes (α-decay, cluster radioactivity and spontaneous fission), it was possible to predict the predominant decay modes of Superheavy nuclei.